100 lat systemu pomocy społecznej w Polsce - Brenk, Mikołaj; Chaczko, Krzysztof; Pląsek, Rafał (Biuletyn Historii Wychowania, 2018)
The goal of this article is to sum up the past hundred years of the social security system in Poland, starting with establishment thereof as Poland regained statehood in 1918. The changes which occurred in that time have been divided into three subsequent stages of the history of the Polish social security system. The first was the Interwar period when efforts were made to establish a social security system in independent Poland, in areas formerly divided between Austria, Prussia and Russia with extreme systems of social security. The next period was the Polish People’s Republic (1944–1989) when the communist authorities dismantled the pre-war social security system based on cooperation between state-owned and social organisations and the Church, replacing it with inefficient structures interested only in selected social groups in need. On the other hand, the third stage, commenced in 1989, of reconstructing social security, at first offered social protection for individuals affected by the system transformation. The last dozen or so years of development of social security is characterised by increasingly visible stimulation of social and economic growth to activate people from the fringes of the society.